Internal Quality Control Practices in Coagulation Laboratories: recommendations based on a patterns‐of‐practice survey. (24th June 2015) - McFarlane, A.; Aslan, B.; Raby, A.; Moffat, K. A.; Selby, R.; Padmore, R.
Summary: Introduction: Internal quality control (IQC) procedures are crucial for ensuring accurate patient test results. The IQMH Centre for Proficiency Testing conducted a web‐based survey to gather information on the current IQC practices in coagulation testing. Methods: A questionnaire was distributed to 174 Ontario laboratories licensed to perform prothrombin time (PT) and activated partial thromboplastin time (APTT). Results: All laboratories reported using two levels of commercial QC (CQC); 12% incorporate pooled patient plasma into their IQC program; >68% run CQC at the beginning of each shift; 56% following maintenance, with reagent changes, during a shift, or with every repeat sample; 6% only run CQC at the beginning of the day and 25% when the instruments have been idle for a defined period of time. IQC run frequency was determined by manufacturer recommendations (71%) but also influenced by the stability of test (27%), clinical impact of an incorrect test result (25%), and sample's batch number (10%). IQC was monitored using preset limits based on standard deviation (66%), precision goals (46%), or allowable performance limits (36%). 95% use multirules. Failure actions include repeating the IQC (90%) and reporting patient results; if repeat passes, 42% perform repeat analysis of all patient samples from last acceptable IQC. Conclusion: Variability exists in coagulation IQC practices among Ontario clinical laboratories. The recommendations presented here would be useful in encouraging standardized IQC practices.